From the Bible to Shakespeare Pantelejmon Kuliš (1819-97) and the Formation of Literary Ukrainian - Danylenko, Andrii (Academic Studies Press, 2016)
This book will stimulate scholarly interest in the Ukrainian language and literature that have faced numerous challenges in the modern period. May be used in university courses on the history of Slavic languages and literatures, contemporary theories of nation-building and national identity as well as language contact and sociolinguistics.